Narratives on why pregnant women delay seeking maternal health care during delivery and obstetric complications in rural Ghana - Joshua Sumankuuro; Memuna Yankasa Mahama; Judith Crockett; Shaoyu Wang; Jeanine Young (BMC, 2019)
Abstract Background Despite the many maternal healthcare policy programmes in Ghana such as free the antenatal care (ANC) and the fee-exemption policy under the National Health Insurance Scheme, among others, the country has yet to make substantial improvements in addressing low skilled care utilisation in pregnancy and delivery. From previous studies, maternal mortality has been linked to women's healthcare decision-making power at the household level in many low and middle-income countries. Thus, a pregnant women's ability to choose a healthcare provider, act on her preferences, and to be sufficiently financially empowered to take the lead in deciding on reproductive and pregnancy care has significant effects on service utilisation outcomes. Therefore, we explored rural community-level barriers to seeking care related to obstetric complications and delivery from the perspectives of mothers, youth, opinion leaders and healthcare providers in Nadowli-Kaleo and Daffiama-Bussie-Issa districts in the Upper West Region of Ghana. Methods This exploratory qualitative study was based on the narratives of women, health providers and community stakeholders regarding the expectant women's autonomy to decide and utilise maternal care. To achieve maximal diversity of responses, purposive sampling procedures were followed in selecting 16 health professionals, three traditional birth attendants and 240 community members (opinion leaders, youth and non-pregnant women) who participated in individual depth interviews and focus group discussions. Results Women's lack of autonomy to seek care without prior permission, perceived quality care of traditional birth attendants, stigmatisation of unplanned pregnancies and cultural beliefs associated with late disclosure of childbirth labour all delayed mothers timely use of skilled care in the study communities. These barriers compounded problems arising from communities that are geographically isolated from hospital care. Conclusions Decisions about seeking maternal care were usually made by the expectant woman's husband and family without providing adequate support to pregnant women during the latter stages of pregnancy and delivery. We conclude that this is primarily a cultural issue. The study recommends a change in the approach to community-level health education campaigns for maximum impacts through the increased involvement of men and families in health service delivery and utilisation.